A rare case of urinary bladder rupture and rupture uterus in an unscarred uterus during vacuum assisted vaginal delivery - ., Latika; Dahiya, Pushpa; Gupta, Anjali; Hooda, Reetu; Dahiya, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Operative vaginal delivery is the use of a vacuum or a forceps device to assist the mother in effecting vaginal delivery of a fetus. The incidence of operative vaginal delivery in U.S.A is 5% or one in 20 deliveries. A 30 year old Para 2 was referred to our institute with complaints of abdominal distension and urinary catheter draining hemorrhagic urine since her delivery. Patient gave history of a Vacuum assisted vaginal delivery three days back at a government hospital. Her previous obstetric history was uneventful. On general examination, she was conscious, with B.P. 110/60 mm of Hg and pulse rate was 84/min. Mild pallor was present. Abdominal examination revealed a distended and tender abdomen. Laparotomy was performed along with a team of general surgeon and Urologists. Rupture of uterus in an unscarred uterus is a very rare entity with an estimated occurrence of one in 8000 to 15,000 deliveries8. Common risk factors for rupture uterus are caesarean section, inappropriate prostaglandin and oxytocin usage, previous instrumental abortion, instrumental delivery, vigorous fundal delivery, etc. Assisted vaginal delivery using vacuum or forceps avoids unnecessary caesarean sections, and thus reduces the associated morbidity. Different studies have proved vacuum is safer than forceps; however expertise is needed for the application of both the instruments.